A new polyploid species of Pleurodema (Anura: Leiuperidae) from Sierra de Comechingones, Córdoba, Argentina and redescription of Pleurodema kriegi (Muller, 1926) - Valetti, Julian Alonso (2009)
We describe a new anuran species of the genus Pleurodema from Sierra de Comechingones, Córdoba province, Argentina and redescribe Pleurodema kriegi with designation of neotype. The new species has lumbar glands and according to its external morphology is cryptic with Pleurodema kriegi. Morphometry, bioacoustics, erythrometry and cytogenetics have allowed differentiating the new species from Pleurodema kriegi. The new species, Pleurodema cordobae, is the single species of its genus with an octoploid chromosomic complement. Its distribution is only known from type locality and two temporary ponds located 5 kilometers away from the former.